Legal regulation improving of environmental audit in the context of the planned codification of environmental legislation - Moroz, Oleg V. (Journal of the Belarusian State University. Law, 2024)
The article reveals the legal issues of environmental audit in the context of the planned codification of environmental legislation. One of such issues is the determination of the place of the provisions regulating it in the structure of both the Law of the Republic of Belarus of 26 November 1992 No. 1982-XII «On environmental protection» and the planned environmental code. It is substantiated that such systematisation the most effective (optimal) is if environmental audit is considered as an element of environmental support for economic and other activities. It is proposed to separate the legal provisions regulating environmental audit within the framework of such support if the latter will be confirmed within the code.